Identification of native coccinellids of San Luis Potosí, for the biological control of Dactylopius spp. - Ascencio Contreras, Daniel Osbaldo; Jarquín Gálvez, Ramón; Lara Ávila, José Pablo (Revista Mexicana de Ciencias Agrícolas, 2018)
The main phytosanitary problem of the nopal vegetable in San Luis Potosí, Mexico is the wild cochineal and the chemical control is inefficient. The present study started from the hypothesis of one of the natural enemies of Dactylopius spp., existing in San Luis Potosí is Chilocorus spp. The objective was to carry out an identification, to establish the basis of a biological control program for conservation. In July 2015, a collection of coccinellids was carried out at the San Ignacio ranch in the municipality of Santa María of Río, SLP. The collection site was a plot of ten hectares, and subdivided into ten subplots of one hectare. A subplot was chosen and an area where there was a greater presence of Dactylopius spp., Which was eighty square meters and approximately 665 plants was sampled. The methodology of Vanegas et al. (2010). Which proposes a sample size of 10 plants taken at random and from each one a cladode, from which the present coccinellids were collected and of these thirty were kept in 70% ethyl alcohol and others alive in breeding chambers. Some collected specimens were taken for identification to the National Reference Center for Biological Control, in Tecoman, Colima, where their morphological and genitalia characteristics were defined, contrasting with the group’s bibliography. The identified coccinellid was Chilocorus cacti, subfamily: Chilocorinae, Tribe: Chilocorini. This is the first complete taxonomic identification of the predator present in nopal vegetable plots in San Luis Potosí, Mexico.
Keywords: Chilocorus cacti; Coccinellidae; Coleoptera; nopal vegetable